Answer:
1
I've attached a screenshot from my graphing calculator of
in blue and
in red. Notice how the red line (inverse function) has (3, 1)
Explanation:
![f(x) = 3^x\\f^(-1)(x) =\ ?\\](https://img.qammunity.org/2023/formulas/mathematics/college/oym1im76mf12nruftqz0potr3afpwtecq2.png)
We must first figure out the inverse function of
which is
![f^(-1)(x)](https://img.qammunity.org/2023/formulas/mathematics/college/waf784241cxsbeinwxex430qxcslo7ew4e.png)
![y = f(x) = 3^x\\y = 3^x\\log\ y = log\ 3^x\\log\ y = x * log\ 3\\x = (log\ y)/(log\ 3)\\](https://img.qammunity.org/2023/formulas/mathematics/college/qoixd77aidx1naahdhgk39edwe3m3ng9tx.png)
We say y = f(x) to begin with, but after find x = ...
we must 'swap' x and y
![x = (log\ y)/(log\ 3)\\y = (log\ x)/(log\ 3)\\](https://img.qammunity.org/2023/formulas/mathematics/college/pipk8nodry122vpmu5ah7j4gtvc46aar0v.png)
![f^(-1)(x) = (log\ x)/(log\ 3)](https://img.qammunity.org/2023/formulas/mathematics/college/7joo2v731hnvd2wrfdol7sld62r1sjuouo.png)
![f^(-1)(3) = (log\ 3)/(log\ 3) = 1](https://img.qammunity.org/2023/formulas/mathematics/college/dx79hgcltjbt3106wyv6bzqux24n5xpcz2.png)